Skuteczne zarządzanie przedsiębiorstwem - Tarczydło, Beata (Effectiveness management of the company, 2006)
The main idea of this paper is to explain what is effectiveness management of the company in still changing market conditions. The paper presents some results of literature studies, market research and own experience connected with discussing problem. Effectiveness management takes care of aims and results, not exactly on methods. It should based on companies characterization and market conditions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 323-329